Spatial and Temporal Analysis of Drought Characteristics in Parambikulam-Aliyar Sub-basin, Tamil Nadu - kumar, R. Vinoth; Arunvenkatesh, S.; Janapriya, S.; Rajasekar, M.; Muthuchamy, I. (International Journal of Bio-resource and Stress Management, 2023)
Drought assessment in a basin provides useful information for sustainable water resource planning and management. The impacts of drought assessment and projection for the Parambikulam–Aliyar sub-basin was carried out with the aid of Regional Climate Models (RCMs) output (precipitation), using the Representative Concentration Pathways (RCPs) 4.5 and 8.5 scenarios of the Fifth Assessment Report (AR5) of the Intergovernmental Panel on Climate Change (IPCC). A basin was divided into four hydrological sub-basins and monthly precipitation data from four stations were used. This study attempts to develop the spatial and temporal pattern of drought characteristics based on frequency and severity of drought events at 3, 6 and 12 month time scales in the Parambikulam-Aliyar sub-basin. A comparison throughout three future time slices reveals a significant decreasing precipitation trend and increasing drought frequency. The Standardized Precipitation Index (SPI) was calculated in order to evaluate the spatial and temporal distribution of droughts by classifying the stations in terms of severely dry and extremely dry conditions as a time percentage. Intensification of drought events is projected for the central and western part of the basin during the last future period under study (2070−2098) under RCP8.5 scenario. The above findings should be taken into consideration for future strategy planning for drought management and for the development of warning systems.